Human Capital in Azerbaijan: Building Competitive Workforce Capacity for Industry 4.0 - Latif Zeynalli (SocioEconomic Challenges)
Human capital is one of the country’s most significant economic metrics. Today, of course, the advancement of technology, the production of inventions, is a result of the human brain. It, in effect, naturally happens in countries with highly evolved human capital. This paper summarizes the arguments and counterarguments within the scientific discussion on the issue priorities of human capital development in Azerbaijan during the industrial revolution. The main purpose of the research is to identify and encourage the improvements in Industry 4.0 in Azerbaijan that would be essential for human capital, as well as to suggest a sustainable workplace outlook for current manufacturing businesses during the modern industrial revolution. The relevance of this scientific problem decision is that given the formation of new mechanisms of development on the eve of the 4th Industrial Revolution, these factors also have an impact on the development of human capital. Because the emergence of new professions during the 4th industrial revolution makes it necessary to form human capital in accordance with these professions. Investigation of the topic in the paper is carried out in the following logical sequence: introducton, literature review, research methodology, empirical findings and conclusions. We used some indicators expressed in the 2008-2017 Global Competitiveness Report of the Azerbaijan World Economic Forum to assess the findings. The object of research is the chosen country is Azerbaijan, because namely here, the development of human capital is one of the main goals of public policy. The paper presents the results of an empirical analysis regression, which showed that regression outcomes show that independent variables can explain 63.2 percent of the heterogeneity in higher education and training in Azerbaijan. Calculations of parameters indicate that any change of 1 percent in the independent variable will increase by 0.341 percent. The results of the study suggest that progressive reforms in Azerbaijan’s higher education and training have had a major effect. To meet the requirements of the Fourth Industrial Revolution, spending on human capital must be increased. The results of the research can be useful for in the direction of formation of competitive human capital and creation of modern innovation space in the coming years.